2017
DOI: 10.1007/s40259-017-0219-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cross-reactivity of Antidrug Antibodies to CT-P13 and Infliximab Reference Product (Remicade): An Analysis Using Immunoassays Tagged with Both Agents

Abstract: BackgroundDuring two pivotal clinical trials of the infliximab biosimilar CT-P13 (PLANETAS and PLANETRA), antidrug antibodies (ADAs) and neutralising antibodies (NAbs) were detected in the sera of patients treated with CT-P13 and the reference product (RP; Remicade).ObjectiveThe aim was to assess the comparability of Remicade- and CT-P13-tagged immunoassays for the detection of ADAs and NAbs using data from these trials, in order to determine the cross-reactivity of CT-P13 and RP ADAs.MethodsSera from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…Several studies have investigated the immunogenic profile of the infliximab RP and one of its biosimilars CT-P13 (Remsima/ Inflectra) and the cross-reactivity of ADAs between both products. 7,[78][79][80] These studies provided similar results in support of the immunogenic similarity between the infliximab RP and CT-P13 in IBD 80,78 or rheumatic diseases. 7,79 It was shown that ADAs against the RP recognized and reacted to the biosimilar in a similar way, indicating that these products share similar immunodominant epitopes.…”
Section: Cross-reactivity Of Antidrug Antibodies Between Rps and Biossupporting
confidence: 67%
See 1 more Smart Citation
“…Several studies have investigated the immunogenic profile of the infliximab RP and one of its biosimilars CT-P13 (Remsima/ Inflectra) and the cross-reactivity of ADAs between both products. 7,[78][79][80] These studies provided similar results in support of the immunogenic similarity between the infliximab RP and CT-P13 in IBD 80,78 or rheumatic diseases. 7,79 It was shown that ADAs against the RP recognized and reacted to the biosimilar in a similar way, indicating that these products share similar immunodominant epitopes.…”
Section: Cross-reactivity Of Antidrug Antibodies Between Rps and Biossupporting
confidence: 67%
“…7,[78][79][80] These studies provided similar results in support of the immunogenic similarity between the infliximab RP and CT-P13 in IBD 80,78 or rheumatic diseases. 7,79 It was shown that ADAs against the RP recognized and reacted to the biosimilar in a similar way, indicating that these products share similar immunodominant epitopes. Additional epitopes (e.g., due to differences in the glycosylation pattern, impurities, or aggregations) may not be excluded, but data suggest that the epitopes that are involved in the immune response to the RP are also present for CT-P13.…”
Section: Cross-reactivity Of Antidrug Antibodies Between Rps and Biossupporting
confidence: 67%
“…The pros and cons are briefly discussed in the above literature analysis. A notable published case example to support the use of the one-assay approach is Remsima ® where both the one-and two-assay approaches were applied without any difference in outcome [22]. Based on our experiences in various biosimilar programs, we view using the biosimilar as labeling reagent and also as confirmatory quenching reagent in a one-assay approach as a conservative strategy suitable for a similarity immunogenicity exercise.…”
Section: Discussionmentioning
confidence: 99%
“…However, the stringent scientific proof of physicochemical and functional comparability is also key to substantiating the conclusion of equivalent immunogenicity. Conclusive molecular overlap between biosimilars and reference medicines is well‐illustrated by the finding that anti‐drug antibodies (ADA) cross‐react equally with both products . Although analytical comparability is reassuring on its own, reference regulatory bodies require case‐by‐case, pre‐ and post‐authorization immunogenicity‐targeted assessment plans .…”
mentioning
confidence: 99%
“…Conclusive molecular overlap between biosimilars and reference medicines is well-illustrated by the finding that anti-drug antibodies (ADA) cross-react equally with both products. 17 Although analytical comparability is reassuring on its own, reference regulatory bodies require caseby-case, pre-and post-authorization immunogenicity-targeted assessment plans. 18 Accordingly, over many years of pharmaceutical surveillance of biosimilar safety and efficacy in European countries, including switching scenarios in Nordic countries 15,19 and more recently in the United Kingdom, 20 no unexpected alerts or warnings have been raised regarding the development of ADA, or any other adverse effect, as a result of the presence of biosimilars on the market.…”
mentioning
confidence: 99%